ANIMISME DAN DINAMISME MASYARAKAT JAWA DALAM RUBRIK ALAMING LELEMBUT MAJALAH PANJEBAR SEMANGAT EDISI JANUARI-JUNI 2022 - Widihastuti, Rahma Ari (Arbitrer : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Javanese people adhered to animism and dynamism long before they knew religion. Even after embracing religion, the practice of animism and dynamism is still firmly attached. The genre of stories that smell mystical, horror, and related to animism and dynamism is still very sustainable in mass media and is still in great demand. This study aims to identify the types of animism and dynamism beliefs that are still inherent in Javanese life, describe their meaning and function. The approach used is qualitative with descriptive methods, data collection techniques in the form of literature study techniques and data analysis techniques in the form of data reduction, data presentation, and conclusions. The source of the research data comes from 25 stories in the Alaming Lelembut rubric of Panjebar Semangat magazine, January-June 2022 edition. The results of the study were several types of animist beliefs: 1) spirits (genderuwo, wewe) waiting for old places; 2) haunted place waiters who get angry when harassed; 3) Sacrifice of wealth; 4) The spirits of the deceased are still wandering because there are unresolved things in the world. While dynamism is in the form of belief in sacred places that can bring wealth (ngalap berkah). The meaning and function of the belief is that there are still many mystical things that are believed and feared by the Javanese people, the existence of the belief to provide understanding and remind that there are other forces that coexist with humans. Javanese people agreed to continue to build this culture as a manifestation of the awareness of the need to remind themselves not to be greedy people and always remember that there are other entities that need to be respected in this world. Keywords: animism, dynamism, alaming lelembut